2012
DOI: 10.1021/ma300735w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Aliphatic Polyamide Dendrimers Based on Facile Convergent Method

Abstract: A novel and rapid approach for the synthesis of aliphatic polyamide dendrimers, consisting of the 3,4-dialkoxyhydrocinnamamide structure as a repeating unit, has been developed. Aliphatic polyamide dendrons and dendrimers were easily prepared by a convergent approach involving activation of a carboxylic acid at the focal point using (2,3-dihydro-2-thioxo-3-benzoxazolyl)phosphonate (DBOP) as the activating agent, followed by condensation with an unprotected AB2 building block. Dumbbell-shaped and star-shaped th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…To this end, many different approaches have been pursued. 4 In most of the cases, hypermonomers are employed that exploit the simplicity of Michael additions, 5 acid-amine conjugations, 6 thiol-ene photoadditions 7 and click chemistry. 8 The "onion peel" dendrimers described by Roy et al provide a noteworthy example.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, many different approaches have been pursued. 4 In most of the cases, hypermonomers are employed that exploit the simplicity of Michael additions, 5 acid-amine conjugations, 6 thiol-ene photoadditions 7 and click chemistry. 8 The "onion peel" dendrimers described by Roy et al provide a noteworthy example.…”
Section: Introductionmentioning
confidence: 99%
“…15 Such polyamides offer a wide range of properties including transparency, outstanding strength-to-weight ratios, high thermal resistance, and good barrier and solvent resistant properties, respectively. [16][17][18][19][20][21] In our latest work, a novel biobased semi-aromatic polyamide (BPA) derived from nonanedioic acid and aromatic diamine containing a pyridine group has been synthesized and characterized. 22 However, it has been found that while the use of conventional nanoclay (Cloisite 30B) can slightly improve the ame retardancy of BPA materials, it also severely decreases their mechanical properties.…”
Section: Introductionmentioning
confidence: 99%